2019
DOI: 10.1002/acn3.713
|View full text |Cite
|
Sign up to set email alerts
|

rt‐PA with remote ischemic postconditioning for acute ischemic stroke

Abstract: Objective To investigate the feasibility and safety of remote ischemic postconditioning ( RIPC ) in acute ischemic stroke patients after intravenous recombinant tissue plasminogen activator (rt‐ PA ) thrombolysis ( IVT ). Methods We performed a pilot randomized trial involving acute ischemic stroke patients with IVT . The patients were randomized 1:1 to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 32 publications
1
78
0
Order By: Relevance
“…Among the 31 publications identi ed on Pubmed search, nine articles were not related to stroke (29%), four articles applied chronic PostRIC (13%), three articles were reviews of literature, three articles described design of the studies or protocols (14)(15)(16), two articles were on subarachnoid hemorrhage patients, one article was a sub-study and four articles were not eligible. After applying the inclusion criteria (acute ischemic stroke-AIS patients and application of remote ischemic perconditioning-RIPerC) and the studies that accept inclusion beyond 48 hours from the onset of symptoms were exclude; a total of 6 articles were included and analyzed in the systematic review (16)(17)(18)(19)(20)(21), note that 4 out of the 6 papers were previously registered as clinical trials (18)(19)(20)(21). Twenty-seven randomized clinical trials (RCTs) were identi ed on clinicaltrials.gov.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 31 publications identi ed on Pubmed search, nine articles were not related to stroke (29%), four articles applied chronic PostRIC (13%), three articles were reviews of literature, three articles described design of the studies or protocols (14)(15)(16), two articles were on subarachnoid hemorrhage patients, one article was a sub-study and four articles were not eligible. After applying the inclusion criteria (acute ischemic stroke-AIS patients and application of remote ischemic perconditioning-RIPerC) and the studies that accept inclusion beyond 48 hours from the onset of symptoms were exclude; a total of 6 articles were included and analyzed in the systematic review (16)(17)(18)(19)(20)(21), note that 4 out of the 6 papers were previously registered as clinical trials (18)(19)(20)(21). Twenty-seven randomized clinical trials (RCTs) were identi ed on clinicaltrials.gov.…”
Section: Resultsmentioning
confidence: 99%
“…Of these RCTs, 6 (22.2%) applied PostRIC and 4 (14.8%%) were not considered after inclusion/exclusion criteria were applied. 17 RCTs were further considered in the present systematic review (NCT0097596 (21), RESCUE-BRAIN (15,22), REVISE-1 (18), rtPA-RIC1 (19),…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that RIC can reduce myocardial infarct size in patients with ST-elevation myocardial infarction treated by thrombolysis and that it can increase myocardial salvage in patients with acute myocardial infarction 29,30 . Accumulating evidence has revealed that RIC also plays a protective role in brains subjected to ischemia [31][32][33][34][35][36] . RIC can be divided into three types according to the onset time: (1) RIPC, in which RIC starts before the onset of brain ischemia; (2) RIPerC, in which RIC starts after the onset of ischemia and before reperfusion of the brain; and (3) RIPostC, in which RIC starts during the reperfusion period 12 .…”
Section: Discussionmentioning
confidence: 99%